Information seeking in electronic environments - Marchionini, Gary (Cambridge series on human-computer interaction, 1995)
Computers and telecommunications technology have extended our regard for information and are driving changes in how we learn, work, and play. This book considers how electronic technologies have changed these skills and strategies and augmented the fundamental human activity of information seeking. Based on 10 yrs of user studies, a human-centered framework for the study of information seeking is developed and illustrated with examples from manual and electronic settings. "Information Seeking in Electronic Environments" is essential reading for researchers and graduate students in information science, human-computer interaction, and education, as well as for designers of information retrieval systems and interfaces for digital libraries and archives.